1989
DOI: 10.1016/0735-1097(89)90347-1
|View full text |Cite
|
Sign up to set email alerts
|

Laser-assisted thermal angioplasty in human peripheral artery occlusions: Mechanism of recanalization

Abstract: Recanalization of completely occluded superficial femoral or popliteal arteries was attempted in 18 patients with use of an Argon laser-mediated thermal probe. The length of the occluded segments varied between 0.5 and 26.0 cm, but 67% of the occlusions were greater than 9 cm long. The initial success rate was 67%. Arterial perforation occurred in six patients but was not associated with major complications. To study the mechanism of the laser-mediated thermal probe, thermal recanalization was performed on 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

1990
1990
1995
1995

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(6 citation statements)
references
References 20 publications
0
5
1
Order By: Relevance
“…On the other hand, most occlusions are due to white fibrous or fibrocalcific plaque which are detected with a high degree of sensitivity by fluorescence spectroscopy [47,481. It is interesting to note that the recanaliza-tion channel through the occluded arterial segments was often centrally located. This is in contrast to the findings of Tobis et al [49] that mechanical and thermal recanalization devices appear to follow a recanalization path along the plane between the intimal plaque and the media. Fluorescence spectroscopy guidance that necessitated redirection of the fiberoptic when media fluorescence was detected may have enabled a more centrally located recanalization channel.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, most occlusions are due to white fibrous or fibrocalcific plaque which are detected with a high degree of sensitivity by fluorescence spectroscopy [47,481. It is interesting to note that the recanaliza-tion channel through the occluded arterial segments was often centrally located. This is in contrast to the findings of Tobis et al [49] that mechanical and thermal recanalization devices appear to follow a recanalization path along the plane between the intimal plaque and the media. Fluorescence spectroscopy guidance that necessitated redirection of the fiberoptic when media fluorescence was detected may have enabled a more centrally located recanalization channel.…”
Section: Discussioncontrasting
confidence: 99%
“…These complex plaques are characterised by a thin fibrous cap overlying soft atheromatous debris. It has been shown that the path of recanalisation of these total occlusions may just as easily be through the soft atheromatous debris after the thin fibrous cap has been ruptured or crossed during gentle probing, as through the true lumen occluded by thrombus [23]. The stiff nature of the Terumo shaft, associated with its ability to seek the path of least resistance due to its hydrophilicity, may contribute to its ability to cross such lesions when fibrocellular organisation of the thrombus has already occured.…”
Section: Foiiow-upmentioning
confidence: 99%
“…Additionally, the delegation of this procedure to a few physicians, to surpass the learning curve, is of inestimatable importance. 2,7 Certainly, this aspect has contributed to improvement in our procedural success and complication rates despite tackling longer lesions in our later experience.…”
Section: Resultsmentioning
confidence: 96%